Evaluation of the NHS active 10 walking app intervention through time-series analysis in 201,688 individuals - Dharani Yerrakalva; Samantha Hajna; Soren Brage; Simon J. Griffin (npj Digital Medicine)
Abstract Despite widespread interest in integrating mobile health apps into primary care to prevent and manage physical inactivity-related health conditions, the effectiveness of these apps remains unclear. We quantified the effects of Active 10 (a goal setting and self-monitoring app developed by Public Health England) on brisk and non-brisk walking using a single-group interrupted time-series analysis of individual-level data collected between July 2021 and January 2024. Among Active 10 users (n = 201,668 l; 51.4 ± 14.4 years; 75.4% women) brisk and non-brisk walking increased by 9.0 (95% confidence interval (CI) 8.9, 9.1; 73% above baseline) and 2.6 min/day (95% CI 2.4, 2.8; 9% above baseline), respectively, on the day of app download. Post-download, brisk and non-brisk walking decreased by 0.15 (95% CI −0.17, −0.13) and 0.06 (95% CI −0.08, −0.03) min/day/month, respectively, but remained above baseline. Our findings suggest that Active 10 may be effective in facilitating increases in brisk and non-brisk walking.